2011
DOI: 10.1248/bpb.34.704
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Motility of the Lower Esophageal Sphincter in a Rat Model of Gastroesophageal Reflux Disease May Be Mediated by Reductions of Serotonin and Acetylcholine Signaling

Abstract: The pathogenesis of gastroesophageal reflux disease (GERD) is multifactorial but the main factor is extended exposure to gastric acid. The extent of esophageal mucosal injury is determined by the degree and duration of esophageal exposure to acid. Patients with GERD have been found to have delayed acid clearance times that are 2-3 times longer than those without GERD. 1) Indeed, the process of esophageal acid clearance is an important factor in the worsening of esophageal mucosal injury. 2) Impaired esophageal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…However, treatment with prokinetic agents has been shown to improve several symptoms in patients with GERD (16,39), and we have recently demonstrated that cisapride improves the motility proximal to the lower esophageal sphincter in GERD rats (40). These findings suggest that gastrointestinal dysmotility is involved in GERD progression.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, treatment with prokinetic agents has been shown to improve several symptoms in patients with GERD (16,39), and we have recently demonstrated that cisapride improves the motility proximal to the lower esophageal sphincter in GERD rats (40). These findings suggest that gastrointestinal dysmotility is involved in GERD progression.…”
Section: Discussionmentioning
confidence: 63%
“…GERD was surgically induced in rats according to the method of Omura et al (36,40). In brief, rats were first anesthetized with ether after 24 h of fasting, and then laparotomy was then performed at the midline.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced ACh concentrations and signalling can lead to a reduction in lower oesophageal sphincter function and subsequently to gastro-oesophageal reflux disease [85]. Additionally, a recent study on cats revealed that the NNCS could also contribute to gastro-oesophageal reflux disease by e.g.…”
Section: Digestive Systemmentioning
confidence: 99%
“…and the clinical importance of this junction have been studied in several species, including dogs [Alsafy and ElGendy, 2012], frogs [Yoshida, 2001], opossums [Seelig and Goyal, 1978], rats [Saegusa et al, 2011], cats [Al-Tikriti et al, 1987], house musk shrews [Takeuchi and Yoshioka, 2004] and humans [Nakanishi et al, 2007]. The closeness of the least shrew to primates including humans provides an excellent research model for functional physiological and pharmacological studies.…”
mentioning
confidence: 99%
“…Furthermore, there is considerable interest in the pathophysiology and pharmacology of the LES [Pratschke et al, 2004]. Numerous drugs, neurotransmitters and hormones can act via several different receptors to exert effects on the LES [Barnette et al, 1992;Saegusa et al, 2011]. A better understanding of the LES junction may shed further light on therapeutic approaches for the treatment of gastroesophageal reflux disease and vomiting [Darmani and Ray, 2009;Gershon 2013].…”
mentioning
confidence: 99%